Science Parks and Responsible Innovation - Gyurkovics, János; Lukovics, Miklós; Udvari, Beáta (Marketing & Menedzsment, 2018)
THE AIMS OF THE PAPER For a long time, science parks have been considered as important economic development initiatives connected to knowledge-creating institutions. They are perceived to significantly contribute to technology transfer activities and new venture formation. So, with gathering the key innovative players and facilitating innovation processes, science parks may also shape the formation of attitudes towards innovation. A new line of thinking has popped up in innovation studies which have placed responsibility into the focus of its interest. This emerging notion of Responsible Research and Innovation (RRI) deals with several oft neglected dimensions of the innovation process such as ethical, societal or environmental fields. The concept of RRI can put into practice more easily in science parks since these are spaces of innovation where a higher concentration of innovative players can be found. Thus, our study aims to theoretically examine how the concept of RRI in general can be applied in science parks METHODOLOGY Literature review is used to present a theoretical approach of the roles of different science park generations in terms of RRI uptake. MOST IMPORTANT RESULTS In first and second generation science parks universities drive the uptake of RRI while in third generation science parks, owing to the players’ mutual dependence and the interactive mode of innovation, RRI efforts are initiated via common decisions and projects between different partners. PRACTICAL/POLICY RECOMMENDATIONS Universities connected to science parks have a crucial role in science education as an RRI key, thus their involvement may contribute to better understand innovation process and the responsible way of innovation activities. Further policy recommendations for governments is to regulate innovation processes based on the concept of RRI, e.g., a government may require open public debates on a scientific result, or may motivate universities to better engage the public or offer easily understandable scientific education/training to the public.